2015
DOI: 10.1021/acssuschemeng.5b00925
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Morphological Changes in Kraft Lignin during Hydrothermal Carbonization

Abstract: In this paper we have investigated the changes in kraft lignin structure and morphology upon hydrothermal carbonization (HTC) at 240°C with and without the presence of carbonization catalysts. The main conclusion of this study is that the structure of kraft lignin was altered only slightly during the hydrothermal carbonization. The main changes in the kraft lignin's structure were demethylation and dealkylation as well as cleavage of β-O-4 bonds. The final product had a more thermally stable and complex cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(79 citation statements)
references
References 34 publications
2
74
1
2
Order By: Relevance
“…The results demonstrated that solvents with poorer polarity benefited the improvement of char yield and carbon recovery. Char yield and carbon recovery of E‐260 from supercritical ethanol were 48.0 % and 57.9 %, respectively, higher than that of W‐260 (41.1 % and 46.9 %) from subcritical water, while the addition of H 2 SO 4 and NaOH remarkably improved the production of biochars . All solvothermal carbon from lignin had small or even no BET surface area (0.4‐2.8 m 2 g −1 for alcohothermal carbon), but certain content of oxygen‐containing functional groups (Figure ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The results demonstrated that solvents with poorer polarity benefited the improvement of char yield and carbon recovery. Char yield and carbon recovery of E‐260 from supercritical ethanol were 48.0 % and 57.9 %, respectively, higher than that of W‐260 (41.1 % and 46.9 %) from subcritical water, while the addition of H 2 SO 4 and NaOH remarkably improved the production of biochars . All solvothermal carbon from lignin had small or even no BET surface area (0.4‐2.8 m 2 g −1 for alcohothermal carbon), but certain content of oxygen‐containing functional groups (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…Nowadays, the preparation of carbon‐based functional catalysts from renewable bioresources such as waste lignin through hydrothermal route has received increasing attentions . Hydrothermal carbonization of lignin produces biochars with lower BET surface, thermally stable char structure and irregular or melted morphology, and has many advantages such as high oxygen functionality of the obtained chars . Solvents play critical role in the carbonization and other solvothermal conversion of lignin .…”
Section: Introductionmentioning
confidence: 99%
“…The most advanced analytical methodologies allowed the identification and structural characterization of low molecular weight species, e.g., the lignin p -bis(2,6-dimethoxyphenol)yl dimers [ 39 ], but also characterization of the differences between native lignins [ 40 ] and technical lignins resulting from the above-mentioned processing [ 41 , 42 , 43 , 44 , 45 , 46 ] ( Figure 4 ).…”
Section: Main Sources Of Natural Phenol Polymersmentioning
confidence: 99%
“…16 It is a complex reaction, performed in a closed system using wet, carbohydrate rich biomass as raw materials under conditions of temperature (180-260 C) and high autogenous pressure. 17 At present, hydrothermal carbonization is predicted a large potential in the preparation of carbon materials or carbon composites with different properties. Some researchers use hydrothermal carbonization to hydrolyze viscous organic substances in sludge at a certain temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%